PENYUSUNAN LAPORAN KEUANGAN RUMAH IBADAH SESUAI DENGAN PSAK 45 PADA SISWA-SISWI SEKOLAH MENENGAH KEJURUAN MATHLAUL ANWAR PROGRAM STUDI AKUNTANSI - Sri Rahayu; Khairunnisa; Dini W. Hapsari; Eksi Puspita R (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2019)
Accountability in organization is very important to assess the performance of an organization both in sectors that aim for profit motive or non-profit motive or non-profit, in this case including the accountability of worship house managers who are organizations included in the category of non-profit organizations. Until now there are very few houses of worship that have financial reports that are in accordance with accounting guidelines, which are listed in PSAK 45. The form of accountability reports currently owned is limited to cash flow in and out only so that the financial position is not listed very needed to describe comprehensively. This happens because various obstacles include the lack of understanding of the management and young human resources as cadres in matters of management. In this service program knowledge and training are provided for students and students of the Mathlaul Anwar Accounting Study Program. The method used is giving explanations of material in the form of lectures, discussions and practices for preparing House of Worship Financial Statements. And as an outcome of this service program, students can understand the management, preparation and accountability of received people's funds. From the results of the questionnaire which was the feedback of the implementation of the activities, the participants felt agreed that this activity was in accordance with the needs of the community, and from pre test and post test have been processed showing that there are differences in knowledge and understanding between before and after the service program activities are carried out.